Fostering a Synergistic Approach to Curriculum Development and TVET-Engineering Qualifications - Mohd Affandi, Haryanti; Sohimi, Nurul Eizzaty; Subri, Ummu Sakinah; Lázaro Moreno Herrera; Yunus, Faizal Amin Nur (Journal of Technical Education and Training, 2024)
The involvement of various stakeholders, aligning diverse interests, and evolving industry requirements are some areas that need careful consideration. The dynamics of power and authority between collaborating partners can affect the efficacy of the collaborative relationship; hence, further study is required to identify obstacles in such partnerships and propose solutions for overcoming them. This project seeks to build a collaboration paradigm between the TVET engineering sector and the industry, emphasizing curriculum development and TVET engineering credentials. This quantitative study employs a survey to collect information from 115 Malaysian technologists in three fields. Simple random selection assures accurate demographic representation and an even distribution of bias. A questionnaire was developed and validated by four experts. Data was evaluated using PLS-SEM 3.3.9 software, algorithms, bootstrapping, and blindfolding techniques. The measurement model evaluates the items’ precision under validity and reliability requirements. The results indicate a significant relationship between the certification system and curriculum development, with a p-value of 0.00. The model has a high predictive power value of R2 = 0.787%, with a significant contribution from the free extract. The influence of size is likewise considerable, with a f2 value of 0.46, but the effect of curriculum TVET is minor, with a f2 value of 0.023. With a Q2 value of 0.601, the predictive significance of the model is validated, indicating its capacity to anticipate events reliably. The findings give valuable insights into the predictive validity of the model and its possible curriculum development applications. The qualification system shapes curriculums, promotes lifelong learning, and bridges the gap between academic and vocational education. However, a deliberate effort is required to overcome obstacles such as lack of coordination, scarce resources, and low public awareness. Higher education institutions must proactively connect their curricula with the certification system’s criteria and industry’s needs to appropriately educate students and guarantee that their skills meet labor market expectations.